The Role of Brown Rice in Farmers’ Income and Consumption in North Kulisusu Subdistrict, North Buton Regency - Azhar, Novita Rahmadani; Fyka, Samsul Alam; Sudarmo, Hadi (International journal of technology and education research, 2026)
This study analyzes the role of brown rice on the income and consumption of farming households in North Kulisusu District, North Buton Regency. The research sample included all 44 brown rice farmers, with data collection through observation, interviews, and documentation. The research area consists of lowlands to hills, partly coastal, with a tropical climate, and the majority of the population earns a living as farmers. Farming is carried out traditionally starting from land preparation, planting with a spacing of 30 × 30 cm, maintenance, until harvesting 1–2 weeks after being ready. Respondents are of productive age, mostly elementary school graduates, have more than 10 years of farming experience, and manage 0–1 hectare of land. The results show an average production cost of IDR 1,097,245 per year with a net income of IDR 4,855,028 per year, indicating a significant contribution of brown rice to farmer income. Of the average production of 220.5 kg per year, 9.81% is consumed by households and the remainder is marketed. Brown rice serves as a source of income and food. Improved efficiency of farming practices, land diversification, and support from the government and relevant institutions are recommended to increase yields, incomes, and local food consumption. This study confirms the economic and health potential of red rice cultivation in the region